18
$\begingroup$

Clearly the kernel of a group homomorphism is normal, but I often hear my professor mention that any normal subgroup is the kernel of some homomorphism.

This feels correct but isn't entirely obvious to me.


One thought I had is that for any normal subgroup $N$ of $G$, we could define the quotient homomorphism $\pi:G\to G/N$ since $G/N$ is a group.

I was imagining that we could consider $\pi^{-1}:G/N\to G$, whose kernel would then be $N$. However, $\pi^{-1}$ doesn't exist since $\pi$ is not a bijection in general.


So my question is this: is there an obvious way to define a homomorphism whose kernel is an arbitrary normal subgroup of $G$? Or does it depend on the particular group whether you can define such a homomorphism?

$\endgroup$
1
  • 5
    $\begingroup$ No, you more or less have it, the kernel of $\pi\colon G\to G/N$ is $N$. No need to worry about $\pi^{-1}$, or if it exists. $\endgroup$
    – Ben West
    Jul 18 '15 at 23:17
31
$\begingroup$

You only have to consider that $\pi:G\to G/N$, defined by $\pi(x)=xN$, is a homomorphism and the $\ker \pi$ is precisely $N$.

$\endgroup$
2
  • 10
    $\begingroup$ overcomplicating as usual. thanks. $\endgroup$
    – Elliot G
    Jul 18 '15 at 23:18
  • 10
    $\begingroup$ that's why we are meant to be here $\endgroup$
    – janmarqz
    Jul 18 '15 at 23:19
4
$\begingroup$

Anyway, if the kernel is non-trivial, the homomorphism is not injective!

You're confusing the inverse of an isomorphism, and the inverse image of a subset by a map. So, yes, if $N$ is a normal subgroup, it is the kernel of the canonical homomorphism : \begin{align*}\pi\colon G&\longrightarrow G/N,\\ g&\longmapsto gN. \end{align*} Indeed, $\pi^{-1}(\bar 1)=\pi^{-1}(N)=N$.

$\endgroup$
3
$\begingroup$

Your intuition is correct, and unfortunately, yes, $\pi^{-1}$ isn't a function. Could we somehow "make" it one?

Well, one way this is often done with "ordinary" functions, is to treat $f^{-1}$, for a given function $f: A \to B$, as not something like this:

$f^{-1}: B \to A$

but instead considering $f^{-1}$ as a function between power sets:

$f^{-1}: \mathcal{P}(B) \to \mathcal{P}(A)$

where for a subset $Y \subseteq B$, we define $f^{-1}(Y) = X = \{x \in A: f(x) \in Y\}$.

Applying this definition to $\pi^{-1}$, we get:

$\pi^{-1}(e_{G/N}) = \pi^{-1}(N) = \{g \in G: \pi(g) \in N\}$

$= \{g \in G: gN = N\} = \{g \in G: ge^{-1} \in N\} = \{g \in G: g \in N\} = N$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.